Perancangan Sistem Tata Udara Ditinjau dari Aspek Energi dan Biaya pada Bangunan Hotel di Semarang - Agus Marjianto; Dave Mangindaan (Engineering, MAthematics and Computer Science (EMACS) Journal, 2020)
[Design of air conditioning system based on the energy and costs aspect of  hotel buildings in Semarang] Indonesia’s economic growth has been above 5% for the past few years. Tourism industry is one of the sectors that shows a significant progress. The improvement in tourism industry has to be supported with good hospitality industry as well. Air conditioning system is one of the main utilities in a hotel building. The design of the air conditioning system for a hotel building must pay close attention to the thermal comfort factor for the guests, safety factor, and energy and cost efficiency aspect of it. Air conditioning system design consists of cooling load calculation for the hotel, air conditioning system selection, energy and cost calculation using the life cycle cost analysis. The maximum cooling load in this hotel is 3.279 kW. From that cooling load, three alternative systems are being considered, which are the central air conditioning system using chiller machine that has constant flowrate, the central air conditioning system using chiller machine that has variable flowrate, and the split air conditioning system using VRF machine. Energy analysis and life cycle cost analysis for 20 years was performed to be able to decide the best system. From that energy and cost analysis it can be concluded that the second alternative, which is three units of chiller with variable discharge with a capacity of 1,100 kW for each chiller, is the best system for the hotel. This system has an energy consumption intensity value of 118 kWh/m2 per year and total cost of Rp. 87,707,416,390  for a period of 20 years.